Specific increases in urinary excretion of anti-DNA antibodies in lupus mice induced by lysozyme administration: further evidence for DNA-anti-DNA immune complexes in the pathogenesis of nephritis. - Yamamoto, T (1993)
We previously reported that lysozyme electrostatically inhibits the fibronectin-mediated DNA binding to the glomerular basement membrane (GBM) and reduces in situ DNA-anti-DNA complex formation in the GBM in NZB/W F1 mice [1]. In this study, we further noticed significant increases in urinary excretion of anti-DNA antibodies and immune complexes (IC) in lysozyme-treated NZB/W F1 mice. Their clearance ratios of IgG anti-DNA antibody to whole IgG were markedly high compared with those of saline-treated animals. A large number of IgG and C3 positive granules were observed in the tubular cells of NZB/W F1 mice treated with lysozyme. On the contrary, nil or only small amounts of anti-DNA antibodies were detected in the urine of NZB/W F1 mice without lysozyme administration despite a large amount of proteinuria, suggesting entrapment of the antibodies in lupus glomeruli. Lysozyme neither inhibited the binding of anti-DNA antibodies to DNA or heparan sulphate nor did it displace anti-DNA antibodies and IC from the kidney homogenates of lupus mice. It thus appears that the inhibition of DNA binding to the GBM due to lysozyme reduced the entrapment of anti-DNA antibodies in the GBM, resulting in urinary excretion of the antibodies.